Ferroptosis in osteosarcoma: A promising future - Liu, Xiang; Du, Shaowen; Wang, Shengdong; Ye, Kaishan (Frontiers in Oncology, 2022)
The incidence of osteosarcoma (OS) is increasing year by year, and the prognosis of patients with advanced OS is extremely poor due to the tendency of recurrence and drug resistance after surgery. Ferroptosis is a novel form of programmed cell death (PCD), which kills cells through iron-dependent lipid peroxidation. Current studies have shown that ferroptosis is closely related to osteosarcoma and can reduce chemotherapy resistance to a certain extent, which has great therapeutic potential. In this paper, we review the regulatory mechanism of ferroptosis and its research progress in OS, hoping to provide new help for the clinical treatment of osteosarcoma.